Abaycosa a new genus of South American wolf spiders (Lycosidae: Allocosinae) - Laborda, Álvaro (2022)
The taxonomy and systematics of the subfamily Allocosinae are poorly known, especially in South America. In the last century, several species have been described in genera from other subfamilies or transferred to them creating great confusion in the knowledge of Allocosinae. In this study we propose the new genus, Abaycosa gen. nov. to contain two species previously described, Orinocosa paraguensis (Gertsch & Wallace 1937) and Pardosa nanica Mello-Leitão 1941. Additionally, we propose two synonyms, Pardosa flammula Mello-Leitão 1945 as a junior synonym of Abaycosa nanica (Mello-Leitão 1941), comb. nov. and Alopecosa rosea Mello-Leitão 1945 as a junior synonym of Abaycosa paraguensis (Gertsch & Wallace 1937), comb. nov. The results of the phylogenetic analysis using molecular characters place Abaycosa in the subfamily Allocosinae, which is also supported by morphological data. Abaycosa can be distinguished from the remaining Allocosinae by the following characters: in males by the presence of only one distal macrosetae and a patch of flat setae on the tip of the cymbium, in females by the ventral position of the vulval chamber and by the short and stout stalk of the spermathecae.